2023
DOI: 10.3389/fmicb.2023.1302167
|View full text |Cite
|
Sign up to set email alerts
|

Leaf, root, and soil microbiomes of an invasive plant, Ardisia crenata, differ between its native and exotic ranges

Naoto Nakamura,
Hirokazu Toju,
Kaoru Kitajima

Abstract: IntroductionEcological underpinnings of the invasion success of exotic plants may be found in their interactions with microbes, either through the enemy release hypothesis and the enhanced mutualism hypothesis. Whereas recent high-throughput sequencing techniques have significantly expanded our understanding of plant-associated microbiomes and their functional guilds, few studies to date have used these techniques to compare the microbiome associated with invasive plants between their native and exotic ranges.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 71 publications
1
0
0
Order By: Relevance
“…OTU analysis showed that there are significant differences in the microbial community structure of healthy and diseased plants in different regions, but, overall, the disease reduced the diversity of bacterial and fungal communities in Nanqi roots. This result is consistent with previous research, which found that geographical factors could lead to certain differences in the composition and abundance of soil microbial communities in different geographical locations [45]. There are also studies indicating that the specific changes in soil microbial community diversity and structure are related to differences in soil structure and plant type [46].…”
Section: Discussionsupporting
confidence: 92%
“…OTU analysis showed that there are significant differences in the microbial community structure of healthy and diseased plants in different regions, but, overall, the disease reduced the diversity of bacterial and fungal communities in Nanqi roots. This result is consistent with previous research, which found that geographical factors could lead to certain differences in the composition and abundance of soil microbial communities in different geographical locations [45]. There are also studies indicating that the specific changes in soil microbial community diversity and structure are related to differences in soil structure and plant type [46].…”
Section: Discussionsupporting
confidence: 92%